Effect of Zerumbone-loaded nanostructured lipid carrier on canine mammary gland tumour cell line - Foong, Jia Ning (2015)
Zerumbone (ZER) from the rhizomes of the wild ginger, Zingiber zerumbet (L.) Smith, is a natural dietary lipophilic compound with antitumour, antiinflammatory, antioxidant, antimicrobial, antinociceptive, hepatoprotective and immunomodulatory properties. However, therapeutic application of zerumbone is plagued by poor water-solubility and subsequent poor absorption, bioavailability and delivery to target tissues. To overcome this limitation, ZER was loaded into nanostructured lipid carrier (NLC) (ZER-NLC). In this study the anticancer effect of ZER-NLC was determined on a canine mammary gland tumour (CMT-stylo) cell line. It is postulated that loading of ZER into NLC does not compromise the anticancer properties ZER. Using the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay, the proliferation of CMT-stylo cells after treament with 1.7 mM of ZER was at 64.30±9.87, 42.06±9.00, 37.81±10.04% while with 1.8 mM ZER-NLC at 102.77±12.68, 38.42±9.16, 41.13±11.72% after 24, 48 and 72 hr treatment, respectively. The half maximal lethal dose (LD50) for ZER and ZER-NLC at 72 hr was 100 and 90 μM, respectively. The half maximal growth inhibition dose (GI50) for ZER and ZER-NLC after 72 hr treatment was 20 and 25 μM, respectively. The anticancer effect of ZER and ZER-NLC was also visualised using the acridine orange/propidium iodide double staining method. Zerumbone and ZER-NLC induced apoptosis of CMT-stylo cells as shown by the membrane blebbing, nucleus margination and chromatin condensation. This study, for the first time, shows that ZER-NLC is a potentially effective drug delivery system for the treatment of canine mammary gland tumours. The ZER-NLC is innovative, novel, and safe, for cancer therapy.